2004
DOI: 10.1002/mds.20237
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cognitive effects of bilateral subthalamic stimulation and subcutaneous continuous infusion of apomorphine in Parkinson's disease

Abstract: Bilateral subthalamic deep brain stimulation (STN-DBS) and continuous subcutaneous infusion of apomorphine (APM-csi) can provide a comparable improvement on motor function in patients with advanced Parkinson's disease (PD), but the mechanisms by which both therapies exert their effects are different. We analyzed the cognitive effects of APM-csi. We also compared neuropsychological effects induced by STN-DBS and APM-csi in advanced PD to ascertain the neuropsychological aspects relevant in determining the thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 31 publications
8
55
0
6
Order By: Relevance
“…Specific cognition deficits include impairments of working memory (Saint-Cyr et al, 2000;Higginson et al, 2009;Okun et al, 2009), cognitive processing, visuo-spatial skills and setshifting (Saint-Cyr et al, 2000;Alegret et al, 2001), response inhibition (Witt et al, 2004), or the decoding of facial expressions (Dujardin et al, 2004;Schroeder et al, 2004;Biseul et al, 2005;Drapier et al, 2008). Even when present, the impact of changes in verbal fluency on the quality of life appears to be relatively small (Alegret et al, 2004;Morrison et al, 2004;Montel and Bungener, 2009;Zahodne et al, 2009). Although almost half patients with DBS experience variable degrees of cognitive changes (Higginson et al, 2009), these deficits become 'relevant' in less than 10% treated patients (Castelli et al, 2006;Tir et al, 2007).…”
Section: Non-motor Side Effects Of Stn and Gpi-dbsmentioning
confidence: 99%
“…Specific cognition deficits include impairments of working memory (Saint-Cyr et al, 2000;Higginson et al, 2009;Okun et al, 2009), cognitive processing, visuo-spatial skills and setshifting (Saint-Cyr et al, 2000;Alegret et al, 2001), response inhibition (Witt et al, 2004), or the decoding of facial expressions (Dujardin et al, 2004;Schroeder et al, 2004;Biseul et al, 2005;Drapier et al, 2008). Even when present, the impact of changes in verbal fluency on the quality of life appears to be relatively small (Alegret et al, 2004;Morrison et al, 2004;Montel and Bungener, 2009;Zahodne et al, 2009). Although almost half patients with DBS experience variable degrees of cognitive changes (Higginson et al, 2009), these deficits become 'relevant' in less than 10% treated patients (Castelli et al, 2006;Tir et al, 2007).…”
Section: Non-motor Side Effects Of Stn and Gpi-dbsmentioning
confidence: 99%
“…Assessment of turning on the stimulator improved executive function, but worsened conditional associative and visual conditional learning (Jahanshahi et al., 2000; Pillon et al., 2000). A study comparing the effects on cognition of STN‐DBS and subcutaneous continuous infusion of apomorphine (APM‐CSI) showed that, contrary to APM‐CSI, STN‐DBS produced a worsening in executive functions (Alegret et al., 2004). Functional neuroimaging studies showed that frontal tasks either did not recover or worsened after STN‐DBS over time (Kalbe et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In patients on APO therapy who develop numerous skin reactions, a change to LCIG therapy can be considered. Compared to DBS, APO infusion similarly decreases 'off' time, but not dyskinesias, according to two one-year studies 26,30 and a five-year prospective study. 32 A similar result was seen in a retrospective analysis of LCIG and DBS, but the DBS group was examined stimulation-on/medication-off, which could explain the difference in dyskinesias.…”
Section: Head-to-head Comparisonsmentioning
confidence: 96%
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] The general finding is that APO provides more time in motor states near normal performance and less time in 'off' and dyskinetic states as compared to conventional optimised therapy. Improvement in quality of life (QoL) may accompany the increased 'on' time, but so far publications on this aspect of APO infusion are sparse.…”
Section: Long-term Efficacy With Apomorphine Infusionmentioning
confidence: 99%